التركيب العربي غير القواعدي في ضوءنظرية الأفضليه - Mohd Nizwan Bin Musling (Al-Bayt University, Jordan, 2024)
This study aims at proving the existence of Arabic language structure in the Hadith text which is in contradiction with the grammaror known as La langue. Furthermore, this study explains the application of Optimality Theory to evaluate and describe such Arabic language structure. The result shows the application of Optimality Theory requires two main criteria which are grammatical optimality and linguistic usage optimality. In addition, these two criteria are used to measure as to what extent the structure complies in accordance with the element of optimality. Thus, by applying Optimality Theory, it avoid from the usage of multiple grammar, variety of results and evaluations such as an error and humiliation for wrong language usage. However, it can be categorized as La langue or alternative linguistic forms and plays an important role as a medium of transferring messages which cannot be done by any language structure with correct grammar as a whole.